2004
DOI: 10.1210/en.2004-0659
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Enhances Glucose Tolerance by Mechanisms Other than Reduction of Fatty Acid Accumulation within Skeletal Muscle

Abstract: We hypothesized that improved glucose tolerance with rosiglitazone treatment would coincide with decreased levels of i.m. triacylglycerol (IMTG), diacylglycerol, and ceramide. Obese Zucker rats were randomly divided into two experimental groups: control (n = 9) and rosiglitazone (n = 9), with lean Zucker rats (n = 9) acting as a control group for obese controls. Rats received either vehicle or 3 mg/kg rosiglitazone for 6 wk. Glucose tolerance was impaired (P < 0.01) in obese compared with lean rats, but was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 44 publications
6
51
1
Order By: Relevance
“…Analysis of intramuscular muscle lipids. Skeletal muscle triacylglycerol (TAG), diacylglycerol (DAG), and ceramide contents were determined as outlined previously (12). Blood metabolite measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of intramuscular muscle lipids. Skeletal muscle triacylglycerol (TAG), diacylglycerol (DAG), and ceramide contents were determined as outlined previously (12). Blood metabolite measurements.…”
Section: Methodsmentioning
confidence: 99%
“…that by increasing fatty acid storage in adipose tissue, TZDs enhance insulin sensitivity by reducing the toxic accumulation of lipids in other insulin-sensitive tissues such as skeletal muscle and liver (5). However, there is mounting evidence that rosiglitazone acts to improve insulin sensitivity in the absence of decreased muscle lipid storage in humans (9,27) and animal models of insulin resistance (7,10,12,28), suggesting that lipid steal from muscle may not be necessary for rosiglitazone-induced insulin sensitization. Although some investigations have demonstrated that lipid storage is decreased in muscle after rosiglitazone treatment (3,4,24), rosiglitazone-induced reductions of liver lipid accumulation have been more consistently observed (5,7,9,29).…”
Section: Fig 3 Skeletal Muscle Ampk Activity and Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite intensive research into the role of PPAR␥, the mechanisms by which their synthetic ligands, the thiazolidinediones (TZDs), cause insulin sensitization are incompletely understood. TZDs improve hepatic insulin sensitivity (196), but interestingly, they do not consistently lower lipid content (288). TZDs activate AMPK in skeletal muscle cells by increasing cellular adenine nucleotide levels (153,277).…”
Section: B Thiazolidinedionesmentioning
confidence: 99%
“…where PR is the total protein content/mg muscle, TG is the lipid content/mg muscle, GLY is the glycogen content/mg of muscle, W s is the water (and dissolved solutes) content in 1 mg of muscle ( 17 for EDL and SOL in obese and lean rodents, expressed as mg mg À1 muscle using a molecular weight of 800 Da for an average triglyceride and the value of 3.66 for the ratio of muscle (wet) mass/muscle dry mass. 18 For GLY values, we used the EDL and SOL data of Goodman and Stephenson 18 for the EDL and SOL muscles from the lean animals and the ob/ob gastrocnemius muscle data of Kaidanovich-Beilin and EldarFinkelman 19 for all three muscles from obese animals.…”
Section: Muscle Densitymentioning
confidence: 99%